Could serum intestinal fatty acid-binding protein and citrulline levels be predictive markers of mortality in critically ill COVID-19 patients? - Onuk, Sevda; Ozer, Nurhayat Tugra; Sahin Ergul, Serap; Eryilmaz Eren, Esma; Karakukcu, Cigdem; Sipahioglu, Hilal; Karayol Akin, Aynur; Gundogan, Kursat (The Journal of Infection in Developing Countries, 2025)
Introduction: The global Coronavirus Disease 2019 (COVID-19) pandemic has been demonstrated to cause severe acute respiratory syndrome and is frequently associated with gastrointestinal (GI) manifestations. Intestinal fatty acid binding protein (IFABP) and citrulline have been identified as potential biomarkers of intestinal (dys)function. The present study was undertaken to ascertain the relationship between serum IFABP and citrulline concentrations and mortality in patients with COVID-19. Methodology: This observational study was conducted in the medical intensive care unit (ICU) and included adult patients diagnosed with PCR-confirmed cases of severe acute respiratory syndrome (SARS-CoV-2). Serum citrulline and IFABp concentrations were quantitatively analyzed using an enzyme-linked immunosorbent assay (ELISA) within the initial 24 hours following ICU admission. Results: A total of 85 critically ill patients (mean age: 70.0  12.4 years) were recruited for this study. The mean Acute Physiology and Chronic Health Evaluation (APACHE II) score was 20.0  7.1. In comparison with survivors (n = 48 patients), non-survivors (n = 37 patients) exhibited significantly elevated serum IFABp concentrations (median (interquartile range, IQR): 13.27 [6.41-17.87] vs. 7.23 [3.26-12.25] ng/mL, p = 0.007) and diminished citrulline levels (median (IQR): 7.61 [4.37-8.52] vs. [4.67 (3.34-8.90] nmol/L, p = 0.043). Receiver operating characteristic (ROC) analysis revealed that the cut off value of serum IFABp and citrulline concentrations to predict ICU mortality was 8.15 ng/mL (AUC: 0.722, 95% Cl: 0.611-0.833, p = 0.001) and 5.99 nmol/L (AUC: 0.671, 95% Cl: 0.551-0.791, p = 0.009), respectively. Conclusions: The findings of this study indicate that serum IFABP and citrulline concentrations possess the potential to function as biomarkers for predicting mortality in critically ill patients with confirmed cases of SARS-CoV-2.